1971
DOI: 10.1111/j.1745-4603.1971.tb01013.x
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate, Low Cost Firmness Measuring Instrument*

Abstract: A low-cost, automatic firmness measuring instrument was developed using commercially available components such as: dial gage, dashpot lowering mechanism, weight sets and probe tips. The details of the assembly and the names of parts manufacturers are given. The instrument is an automated modification of the original P-L Meter developed by Parker and Levin at Michigan State University. The application of the instrument to firmness measurements on cherries and tomatoes is summarized and illustrated with typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The acid concn delcines until Nov. and remains more or less constant thereafter (2,3). A similar pattern was described for grapefruit in California (19), Texas (5), and in certain years in Florida (7). Concn of titratable acidity in juice may be stable, but the absolute amount of acid calculated on a per fruit basis actually increases due to fruit growth and accumulation of acid during this time.…”
Section: A D D Itio N a L Index Words C Itrus Paradisi Water Stress F...supporting
confidence: 57%
See 2 more Smart Citations
“…The acid concn delcines until Nov. and remains more or less constant thereafter (2,3). A similar pattern was described for grapefruit in California (19), Texas (5), and in certain years in Florida (7). Concn of titratable acidity in juice may be stable, but the absolute amount of acid calculated on a per fruit basis actually increases due to fruit growth and accumulation of acid during this time.…”
Section: A D D Itio N a L Index Words C Itrus Paradisi Water Stress F...supporting
confidence: 57%
“…The fruit is less palatable when this happens than it was in Nov. There are reports which indicate that acid levels in citrus fruit is related to environmental conditions (4,5,13,15,16,19,20). Rasmussen et al (15), for example, reported a correlation be tween high temp and acid content of young orange fruit, and an inverse relationship between mean acid content of 'Ruby Red' grapefruit and rainfall.…”
Section: A D D Itio N a L Index Words C Itrus Paradisi Water Stress F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other firmness meters for tomatoes, the Firm-a-meter and the Ansco meter were described by Garrett et al (1960). Diener, Sobotka & Watada (1971) measured tomato fruit firmness with a modification of the original . P-L meter.…”
Section: Introductionmentioning
confidence: 99%